Reproductive Problems in Adolescent and Young Adult Gynecology Cancer Survivors: A Systematic Review - Riri Amalina; Yati Afiyanti; Imami Nur Rachmawati (Universitas Aisyah Pringsewu, 2023)
Adolescents and young adults with gynecology cancer are unique, especially in terms of their reproductive and sexual aspects. This systematic review aimed to identify reproductive problems in adolescent and young adult survivors of gynecology cancer. Articles from five databases were reviewed. PubMed, Taylor Francis, Scopus, Science Direct, and Proquest, which were published in 2012-2023, 15-39 years of age, who had gynecology cancer and had completed cancer treatment. Biased risk assessment using Joanna Briggs Institute (JBI) tools. From the 1.167 articles, 12 were reviewed in this systematic review. Based on the results of the study, there were 4479 adolescent and young adult cancer survivors and 990 with gynecology cancer (cervical, ovarian, endometrial, pelvic, and vulva). The average age at diagnosis of cancer was 33,58 years old. Reproductive problems that occur in adolescents and young adults are sexual dysfunction, sexual activity, fertility, and psychosocial problems as a result of reproductive problems. Adolescent and young adult cancer survivors need information on reproductive issues and fertility maintenance after completing cancer treatment. Health professionals must focus on reproductive problems and counselling about long-term reproductive health among adolescent and young adult gynecology cancer survivors.Abstrak: Remaja dan dewasa awal dengan kanker ginekologi punya keunikan khususnya berkaitan dengan aspek seksual dan kesehatan reproduksi. Tinjauan sistematis ini bertujuan untuk mengidentifikasi masalah reproduksi penyintas kanker ginekologi berusia remaja dan dewasa awal. Artikel dari lima database yaitu PubMed, Taylor Francis, Scopus, Science Direct, dan Proquest yang dipublikasi tahun 2012-2023 dengan rentang usia responden 15-39 tahun, memiliki sampel kanker ginekologi dan telah menyelesaikan pengobatan kanker. Penilaian risiko bias menggunakan tools Joanna Briggs Institute (JBI). Jumlah artikel yang didapatkan dari pencarian adalah 1.167 artikel dan sebanyak 12 artikel ditinjau dalam telaah sistematis ini. Berdasarkan hasil telaah didapatkan sebanyak 4479 penyintas kanker berusia remaja dan dewasa awal dengan jenis kelamin perempuan sebanyak 990 penyintas dengan jenis kanker ginekologi (serviks, ovarium, endometrium, pelvis, dan vulva). Rata-rata usia saat diagnosis kanker yaitu 33,58 tahun. Masalah reproduksi yang terjadi pada remaja dan dewasa awal yaitu disfungsi seksual, mengalami gangguan pada aktivitas seksual, masalah fertilitas, dan masalah psikososial sebagai dampak dari gangguan reproduksi. Penyintas kanker remaja dan dewasa awal membutuhkan informasi terkait masalah reproduksi dan persiapan untuk menjaga fertilitas setelah terapi aktif kanker selesai. Tenaga kesehatan harus fokus pada masalah reproduksi penyintas dengan kanker ginekologi dan membutuhkan konseling terkait kesehatan reproduksi jangka panjang.